Strategic Bricolage dalam Komunikasi Pemasaran Digital Musicverse untuk Membangun Keterlibatan Audiens - Gracia Zephaniah; Suparman Suparman (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study analyzes the planning and implementation of digital marketing communication strategies by TSP & Co. through the Musicverse program in building audience engagement. The post-pandemic growth of Indonesia's music festival industry has intensified competition among promoters, reflected in 187 festival events in Jakarta throughout 2025 and a 3,872% audience growth by TSP & Co. over the past decade. Using a descriptive qualitative approach, data were collected through observation and in-depth interviews with internal members of TSP & Co. Findings show that Musicverse's planning follows a strategic bricolage pattern, building strategy from available resources and emerging opportunities rather than a rigid IMC framework. Implementation relies on implicit coordination without formal standard operating procedures, sustained through shared understanding across divisions and leadership-driven integration. Platform differentiation emerges as a critical element, with Instagram serving as the brand's official face and TikTok as a space for content exploration. The TSP Squad community network proves strategically vital in regional expansion outside Java, functioning as a local knowledge bridge, trust network, and organic crisis buffer. This study suggests community-based marketing as a sustainable model for building audience loyalty in adaptive creative organizations through flexible IMC coordination.